Drawing Insights from Japan's Energy Efficiency Policies for Indonesia's Progress - Togar Wiliater Soaloon Panjaitan; Andante Hadi Pandyaswargo; Tinton Dwi Atmaja; Fitria Astuti Firman; Muhammad Indra al Irsyad (Purnomo Yusgiantoro Center, 2024)
As archipelagic countries, Japan and Indonesia's electricity transmission and distribution infrastructures are island-specific. They have limited network areas and face similar risks caused by climate change. Energy conservation through technical approaches to improve energy efficiency is effective in combating climate change and generates more significant economic benefits. This study examines the strategies demonstrated by Japan to improve its energy efficiency and identifies the potential of adopting those strategies in Indonesia. This research includes an in-depth literature review and benchmarking approaches to the two countries' mitigation strategies. The study found that the Japanese approaches, such as the prioritization of strict regulations, extensive use of innovative technology, and solid industrial collaboration, can be adopted to improve energy efficiency in Indonesia. We also identified several obstacles to adopting those approaches in Indonesia, such as policy inconsistencies, limited financial incentives, and fragmented governance. Adopting the Japanese approaches in Indonesia needs clear energy labeling, more integrated energy management in large industries, appropriate electricity pricing, and efficient energy service company (ESCO) schemes.